Characterization of barefoot and shod running - Franzese, R (2018)
Barefoot (BF) and shod (SD) running mark relevant mechanical boundary conditions for affecting running biomechanics. This thesis studies the variation in foot-strike strategy (FSS), and whilst accounting for this variation provides a description of BF and SD running at different aerobic training velocities in uninjured, highly trained competitive (1500 m personal best: mean (standard deviation) = 3:59.8 (10.0)) male distance runners (n = 19). At one velocity, BF running for nine uninjured competitive female runners is also studied. Three dimensional (3D) gait analysis was used to measure lower-limb joint angles during treadmill running, and surface electromyography (EMG) was used to measure lower-leg muscle activity. Generalized linear mixed models (GLMMs) were used to account for and quantify between-subject variation and stride-specific foot-strike angle (FSA). This thesis provides evidence to discourage the general practice of classifying runners in the present population within a FSS group for BF running. Also, a subset of individuals exhibited high FSA variability for BF running, possibly because of discomfort. The hypothesis that FSA correlates with changes in running kinematics was supported. A larger hip width to femur length ratio found in females was associated with more hip adduction, corroborating previous research. More plantarflexed FSA was hypothesized for higher velocities, and flatter foot placement was anticipated for BF versus SD running. Flatter foot placement was observed for BF running, but FSA was independent of velocity for BF running and more foot dorsiflexion at foot-strike (FS) was observed for fast velocity for SD running. These adjustments may be motivated by maximal or sub-maximal deformation of the heel pad and the novelty of BF running. Coupled with the observed increase in gastrocnemius muscle activity for BF versus SD running, these observations may be cause for caution for the novice BF runner. A different coordinative structure for tibia and rearfoot coupling emerged as velocity increased, possibly in response to an increased functional demand of the talocrural and subtalar joints for BF running as velocity increases. The hypothesis that coordinative variability changes with FSA during impact phase, to reflect the underlying elevated injury risk for rearfoot-strike runners, was not supported. Coordinative variability was independent of FSA. In addition, coordination was more robust to changes in velocity and differences in FSA for SD running, possibly reflecting habituation. Running BF may have potential as a diagnostic tool for studying injury etiology, because the limit of no external cushioning may place mechanical demands on the runner sufficient to elicit anomalous running kinematics, which may manifest as high kinematic variability.